Between Kherson and Rome a survey of wall paintings in the Church of St Clement in Stará Boleslav - Dienstbier, Jan; Klípa, Jan 1976-; Pokorný, Adam 1979- (2023)
Comparative study of wall paintings in churches dedicated to St Clement in Stará Boleslav and Rome reveals the wide international networking of contemporary agents in artistic transfer. The importance of late twelfth-century wall paintings in St Clement’s in Stará Boleslav – among Bohemia’s foremost medieval monuments – is underscored by their close proximity to the place of the martyrdom and the center of the cult of the country’s patron, St Wenceslas. The Bohemian church’s consecration echoes the Cyril and Methodius mission, resonating with the transfer of St Clement’s relics from the Crimea to Central Europe, then to the Basilica of San Clemente in Rome. The frescoes in the Roman basilica’s lower church have been recognized as an important source for the concept of the paintings. The extensive, and iconographically exceptional, image cycle of St Clement’s life was commissioned by a high-ranking cleric, possibly the Salzburg archbishop, Adalbert of the Přemyslid family. The recent fresco restoration survey has yielded insights into the painting technique and will become the basis for the future rescue and rehabilitation of the Romanesque church’s wall decoration.